G307(P) Evaluating and reducing paediatrics medication errors based on two audits. "a multidisciplinary approach". (27th April 2015) - Atukorale, DC; Bhatti, A; Jayatunga, R; Ahmed, A
Abstract : Aims: Medication errors occur and are more significant in paediatrics, despite standards being set on safe prescribing (BNF &Trust Prescribing Policy, 2007). Errors are frequent during prescribing, dispensing and administration of medications as shown by the EQUIP study (2009). We aimed to identify the incidence and types of medication errors and implement strategies to minimise these errors. Method: 1 st audit – was carried out to assess prescription charts against thirteen Good Prescribing standards (BNFC), in the inpatient unit. 2 nd audit – A retrospective analysis was done of all incident reporting on paediatric medication errors within the Trust, over a 17 month period (January 2013–May 2014). Different types of medication errors, their location and the severity scoring was identified. The results were compared with a previous similar audit carried out in January 2011–May 2012, after which several interventions were implemented to reduce these errors. Results: Most of "Good Prescribing Practice"standards were met (>80%), except for antibiotic indication and duration (Standard 13) (20%). Total Trust medication errors in January 2013–May 2014 were 10%, out of which paediatric medication errors was 1/5 th . Administration errors (47%) dominated followed by prescription errors (42%). 3% were dispensing errors. Commonest administration error was failure to administer a prescribed medication and the commonest prescribing error was failure to prescribe a recommended medication. Errors on inpatient wards exceeded OPD/Community. Conclusions: A significant reduction (p < 0.05) in paediatric medication errors was seen after the multidisciplinary action plan was implemented, although the overall Trust incident reporting increased. Serious errors were significantly reduced (p < 0.001) and there were no lethal paediatric medication errors during this period. The Root cause analysis and prescribing audit identified a number of interventions, including re-designing the Paediatric drug charts to include antibiotic indication and duration and the launch of the specials project to procure secondary care prescriptions in-house. We conclude that it is possible to reduce medication errors by implementing a multidisciplinary approach.